Quantitative Bone SPECT in Young Males with Delayed Puberty and Hypogonadism: Implications for Treatment of Low Bone Mineral Density - Lubushitzky, Rafael; Front, Dov; Iosilevsky, Galina; Bettman, Lise; Frenkel, Alex; Kolodny, Gerald M; Israel, Ora (The Journal of nuclear medicine (1978), 1998)
Constitutional delayed puberty (DP) and idiopathic hypogonadotropic hypogonadism (IHH) lead to osteoporosis in adult men. We were interested in whether response to treatment of these conditions by testosterone could be predicted by in vivo quantitative bone SPECT (QBS) measurement of bone turnover and whether testosterone administration affects bone mineral density (BMD) in these subjects. In vivo QBS and BMD measurements were performed in the lumbar spine (LS) and femoral neck (FN) of 29 young men with DP and 16 young men with IHH. In vivo QBS and BMD values in these patients were compared to the values obtained from 27 age-matched normal controls. The effect of testosterone treatment was determined by measuring changes in QBS and BMD, before and after treatment of 22 patients with DP and of all 16 patients with IHH. Seven patients with DP were not treated. In vivo QBS values in patients with DP were significantly higher than those in controls (8.44% +/- 2.55%ID/ml compared to 5.63% +/- 1.12%ID/ml x 10(-3), p < 0.001, for the LS; and 7.86% +/- 3.01%ID/ml compared to 4.29% +/- 1.25%ID/ml, p < 0.001, for the FN). One year after testosterone treatment, QBS values in DP were significantly reduced. Pretreatment BMD values in patients with DP were significantly lower than those in normal subjects (0.77 +/- 0.11 g/cm2 compared to 1.03 +/- 0.14 g/cm2, p < 0.0001, for the LS; and 0.89 +/- 0.11 g/cm2 compared to 1.08 +/- 0.18 g/cm2, p < 0.006, for the FN). One year after treatment, BMD values increased significantly (0.91 +/- 0.14 g/cm2, p < 0.0001, for the LS; and 0.97 +/- 0.11 g/cm2, p < 0.0001, for the FN). The seven untreated young men with DP still had significantly lower-than-normal BMD values (0.82 +/- 0.08 g/cm2, p < 0.008, for the LS; and 0.89 +/- 0.05 g/cm2, p < 0.04, for the FN). In patients with IHH, QBS values were not significantly different from those found in normal controls. The values for BMD were significantly lower for both the LS (p < 0.0001) and the FN (p < 0.001). After treatment, BMD values in patients with IHH were still significantly lower than those of normals (p < 0.009 for the LS; and p < 0.006 for the FN). Young men with maturation abnormalities show low bone density. Patients with DP and high bone turnover, as revealed by high QBS values, respond to testosterone treatment. Patients with IHH have normal bone turnover and do not respond to testosterone.